Case of escape in cassava, Manihot esculenta Crantz - Nassar, Nagib Mohammed Abdalla (2017)
Two cassava escapes where collected from cultivated fields near natural habitat in Bolivia. They are described morphologically and analyzed cytogenetically in this study. It is suggested that they are the product of backcrosses of cassava interspecific hybrids with the cultigen itself, and that selective conditions have developed in which certain forms of cassava segregates have adapted to grow wildly in natural habitats near cassava fields. These segregates may hybridize with cultivated cassava upon coming in contact with such varieties. Because these escapes have incorporated useful genes from the wild into their genetic structure, they could be used for cassava improvement since their genetic barriers with other forms of cassava are very weak.